Analisis Akuntabilitas dan Efektivitas Pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) di Desa Sumber Kejayan, Kabupaten Jember - Nur Afifa, Mariyatul; Siswanto, Adil (Lembaga Teewan Journal Solutions, 2026)
The problem in this study is the mismatch between the allocated Village Revenue and Expenditure Budget (APBDes) and the realization of development projects in Sumber Kejayan Village. This research aims to analyze the accountability and effectiveness of APBDes management. A qualitative descriptive approach was used, collecting data through interviews, observations, and documentation. The results indicate that accountability in managing APBDes is relatively good, involving coordination between the village government, the Village Consultative Body (BPD), and the community. However, community participation and understanding remain uneven. Furthermore, the effectiveness of APBDes management is considered quite effective with a budget realization of 97.89%, successfully supporting basic infrastructure. However, economic empowerment programs require further improvement to achieve sustainable development.